Fraud and Corruption in U.S. Nonprofit Entities: A Summary of Press Reports 2008-2011. (December 2015) - Archambeault, Deborah S.; Webber, Sarah; Greenlee, Janet
The charitable sector is vulnerable to fraud losses, with these losses negatively impacting the organization's reputation, future funding, and ability to advance its mission. Research on nonprofit fraud is relatively scarce, due mainly to limited availability of data. We create a database that summarizes and describes basic facts (nature and timing of fraud, description of organization, magnitude of loss, and perpetrators) for 115 incidents of detected fraud occurring in U.S. nonprofit organizations. We find a disproportionately high incidence of nonprofit fraud in the Health and Human Services National Taxonomy of Exempt Entities Groups, a high percentage of females committing misappropriation frauds, and that the organizational role of the perpetrator is related to the size of the fraud loss. We also investigate whether organizations detecting a nonprofit fraud report this information, as required, on Internal Revenue Service Form 990, and find that many organizations do not comply.